The Bible and African culture : mapping transactional inroads - Waweru, Humphrey (Zapf Chancery, 2011)
How can African theology survive the self-repetition of mere cultural apologia or contextualization-stereotypes, and mature into a critical theoretical discipline responding to the challenges of the postmodern world-order? Dr. Humphrey M. Wawe contributes here a sound theological reflection using the hitherto unused methodological paradigm of mapping the inroads in the "transaction" between the Bible and African culture